Net energy value of two low-digestible carbohydrates, Lycasin®HBC and the hydrogenated polysaccharide fraction of Lycasin®HBC in healthy human subjects and their impact on nutrient digestive utilization - Sinaud, S.; Montaurier, C.; Wils, D.; Vernet, J.; Brandolini, M.; Bouteloup-Demange, C.; Vermorel, M. (British journal of nutrition, 2002)
The metabolizable energy content of low-digestible carbohydrates does not correspond with their true energy value. The aim of the present study was to determine the tolerance and effects of two polyols on digestion and energy expenditure in healthy men, as well as their digestible, metabolizable and net energy values. Nine healthy men were fed for 32 d periods a maintenance diet supplemented either with dextrose, Lycasin®HBC (Roquette Frères, Lestrem, France), or the hydrogenated polysaccharide fraction of Lycasin®HBC, at a level of 100 g DM/d in six equal doses per d according to a 3×3 Latin square design with three repetitions. After a 20 d progressive adaptation period, food intake was determined for 12 d using the duplicate meal method and faeces and urine were collected for 10 d for further analyses. Subjects spent 36 h in one of two open-circuit whole-body calorimeters with measurements during the last 24 h. Ingestion of the polyols did not cause severe digestive disorders, except excessive gas emission, and flatulence and gurgling in some subjects. The polyols induced significant increases in wet (+45 and +66 % respectively, P<0·01) and dry (+53 and +75 % respectively, P<0·002) stool weight, resulting in a 2 % decrease in dietary energy digestibility (P<0·001). They resulted also in significant increases in sleeping (+4·1 %, P<0·03) and daily energy expenditure (+2·7 and +2·9 % respectively, P<0·02) compared with dextrose ingestion. The apparent energy digestibility of the two polyols was 0·82 and 0·79 respectively, their metabolizable energy value averaged 14·1 kJ/g DM, and their net energy value averaged 10·8 kJ/g DM, that is, 35 % less than those of sucrose and starch.